Preclinical and clinical evaluation of the liver tumor irreversible electroporation by magnetic resonance imaging - Figini, Matteo (Am J Transl Res, 2017)
Irreversible electroporation (IRE) is a relatively new technique for tumor ablation. It has shown promising results in difficult cases where surgery is not recommended and delicate anatomic structures are present near or within the tumor. Currently, liver cancer is one of the most common targets for IRE treatment. Pre-operative and post-operative imaging has a key role in IRE procedures and research studies. Although ultrasound is usually the first choice, especially for intra-operative guidance, magnetic resonance imaging (MRI) plays an important role in the visualization and characterization of tumor before and after IRE in clinical and preclinical studies. However, the appearance of liver lesions after IRE with different MRI sequences has never been systematically investigated, and the most common practice is to limit the acquisition protocol to only contrast-enhanced T1-weighted images. In this work, the role of MRI in clinical and preclinical assessment of hepatic tumors treated with IRE is reviewed and discussed.